2023
DOI: 10.1021/acs.inorgchem.2c04428
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Zirconium-Based Metal–Organic Framework Crystallinity at Extreme Pressures

Abstract: Recent research on metal−organic frameworks (MOFs) has shown a shift from considering only the crystalline high-porosity phases to exploring their amorphous counterparts. Applying pressure to a crystalline MOF is a common method of amorphization, as MOFs contain large void spaces that can collapse, reducing the accessible surface area. This can be either a desired change or indeed an unwanted side effect of the application of pressure. In either case, understanding the MOF's pressure response is extremely impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…3), see ESI† for the measurement of a standard material (S-32). Silicone oil AP-100 was used as a pressure transmitting medium (PTM), which has previously been applied for HPPXRD experiments of Zr-based MOFs 47 and molecular perovskites. 48 To the best of our knowledge, silicone oil AP-100 acts as hydrostatic, non-penetrating PTM, enabling to study the mechanical response of the MOFs without any additional effects such as penetration of the PTM into the pores of the MOF.…”
Section: Resultsmentioning
confidence: 99%
“…3), see ESI† for the measurement of a standard material (S-32). Silicone oil AP-100 was used as a pressure transmitting medium (PTM), which has previously been applied for HPPXRD experiments of Zr-based MOFs 47 and molecular perovskites. 48 To the best of our knowledge, silicone oil AP-100 acts as hydrostatic, non-penetrating PTM, enabling to study the mechanical response of the MOFs without any additional effects such as penetration of the PTM into the pores of the MOF.…”
Section: Resultsmentioning
confidence: 99%
“…The shift in Bragg diffraction peak positions toward lower 2θ values after PFOA sensing was confirmed by PXRD analysis (Figure S40). This low-angle shift suggests an increase in cell volume after PFOA interaction . To confirm this change, a Pawley refinement was attempted postsensing.…”
Section: Resultsmentioning
confidence: 99%
“…However, Redfern et al also showed that the linker length and the nearest node distance play an important role in the framework response to compression, highlighting how even minor differences in the structure can strongly affect the bulk modulus . One of the key parameters in MOFs structure that defines their topology is the linker connectivity, also known as topicity, which identifies how many metal nodes a single linker molecule can connect to within the MOF network. , Identifying MOFs with the same topology and different linker topicity and comparing their behavior at high pressure could help in assessing the role played by this parameter in the framework mechanical stability …”
Section: Introductionmentioning
confidence: 99%
“…This is due to different experimental methods or the lack of experimental details. As an example, reported values of the UiO-66­(Zr) bulk modulus span between 15 and 37.9 GPa. Such different values are probably the result of different defect concentrations present in the framework, burdensome quantity to determine experimentally. ,, Moreover, it is well known that guest molecules can penetrate into the pores and significantly impact the high-pressure behavior of MOFs and thus the bulk moduli reported in the literature. , A recent study by Redfern and co-workers explores the relationship between the structural parameters of two isoreticular MOF series, the UiO and the NU-900 series. They observe that for both topologies, the bulk modulus is inversely correlated with void fraction, which is in agreement with a computational study showing that the bulk modulus is inversely proportional to the pore diameter for 3000 frameworks .…”
Section: Introductionmentioning
confidence: 99%